2014
DOI: 10.1590/s0104-66322014000100020
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption study of Ni2+ and Cr3+ by Sargassum filipendula: kinetics and equilibrium

Abstract: -In this work, the biosorption of Cr 3+ and Ni 2+ by Sargassum filipendula pre-treated with CaCl 2 was studied. Kinetic and equilibrium experiments were carried out for mono-and multi-component solutions in a batch reactor at pH 3.0 and 30 ºC. The results from the kinetic experiments showed that Cr 3+ adsorbs slower than Ni 2+ . This behavior was explained by means of a mechanistic analysis, which showed that Cr 3+ uptake presented three adsorption stages, whereas Ni 2+ adsorption presents only two. The mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
(48 reference statements)
0
3
0
1
Order By: Relevance
“…The authors found that, for an initial metal concentration of 10 mg.L -1 , the uptake capacity of the moss, at equilibrium, was the same for both metals (4.8 mg.g , the uptake of Pb (II) was higher than 78%. Seolatto et al (2014) , respectively. In the binary system a strong competitive behavior was observed.…”
Section: +mentioning
confidence: 97%
“…The authors found that, for an initial metal concentration of 10 mg.L -1 , the uptake capacity of the moss, at equilibrium, was the same for both metals (4.8 mg.g , the uptake of Pb (II) was higher than 78%. Seolatto et al (2014) , respectively. In the binary system a strong competitive behavior was observed.…”
Section: +mentioning
confidence: 97%
“…Dead algal mass is reported to be more promising than living algae because it has a high metal ion sorption capacity at a high rate, and the adsorbed heavy metal ions present can easily be removed using de-ionized water or desorption agents [106]. There are several works on the use of many species of sargasso as biosorbents, and in the removal of pollutants, such as metal ions (e.g., Hg, Pb, Cu, Cd, Ni, Zn, Fe, and Cr), organic solvents, and organic dyes [107][108][109][110][111][112][113][114][115].…”
Section: Biosorption Potential Of Sargasso Biomassmentioning
confidence: 99%
“…as an efficient biosorbent for the eradication of chromium, cadmium, copper, nickel, zinc, etc. [14]. Previously, Esmaeili and colleagues used activated carbon prepared from red algae Gracilaria and brown algae Sargassum sp.…”
Section: Introductionmentioning
confidence: 99%